4(5x-3)+9=-2

Simple and best practice solution for 4(5x-3)+9=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5x-3)+9=-2 equation:


Simplifying
4(5x + -3) + 9 = -2

Reorder the terms:
4(-3 + 5x) + 9 = -2
(-3 * 4 + 5x * 4) + 9 = -2
(-12 + 20x) + 9 = -2

Reorder the terms:
-12 + 9 + 20x = -2

Combine like terms: -12 + 9 = -3
-3 + 20x = -2

Solving
-3 + 20x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 20x = -2 + 3

Combine like terms: -3 + 3 = 0
0 + 20x = -2 + 3
20x = -2 + 3

Combine like terms: -2 + 3 = 1
20x = 1

Divide each side by '20'.
x = 0.05

Simplifying
x = 0.05

See similar equations:

| (6x+2)(7x^2-5x-4)= | | 2x-10=38 | | -9r+1=-80 | | 3x8/3 | | mx^2+(2m-1)x+(m-1)=0 | | 5=x/4=1 | | 16=-10b+3b | | x^3-5x=-3 | | -8x-8=9x+43 | | 8(y-1)+5(y-1)= | | 5x+9y=-42 | | 2(x+6)-4(-x+3)=3(2x+1)-3 | | 2b*b*3a= | | -3x+2y=-34 | | -8(-x)-4(x-2)=8 | | 3S+45=10 | | 4(y-3)+3=8(2y+5) | | (3x-2y)+8=-15 | | 3x+6(-1)=-30 | | -1x+14= | | 3x^4+x^3+3x^2-29x-10=0 | | 5w+-2.5=-7.5 | | g-2=1/4(4g-2) | | 2B+40=240 | | x^3-7x^2+17x+5=0 | | 17x-9[x+4]=3x-26 | | 0.054x^2+x-0.4=0 | | 14=9+-x | | 14310=5.0625*h*3.14 | | 72-4-14d=36 | | 121.1=1.3-4d | | Tgx=0.04 |

Equations solver categories